Peran Positive Parenting dan Otoritatif Parenting dalam Menurunkan Risiko Kekerasan terhadap Anak Usia Dini - Mulyana, Ade; Kamil, Mustofa (UIR PRESS, 2026)
Background: Violence against early childhood remains a critical issue in the study of child development and family psychology, particularly when parenting practices tend to be harsh, unresponsive, or inconsistent. This study aims to analyze the role of positive parenting and authoritative parenting in reducing the risk of violence against young children based on theoretical reviews and recent empirical findings. The research method used is library research by examining various scientific journals, books, and relevant research results. The findings indicate that both parenting styles contribute to reducing the risk of violence through the application of warmth, responsiveness, non-violent discipline, two-way communication, and consistent rules that support the creation of a safe and harmonious caregiving environment. Positive parenting and authoritative parenting also enhance children's emotional regulation and reduce parental stress, thereby minimizing the potential for aggressive behavior from parents. In conclusion, positive parenting and authoritative parenting are evidence-based strategies that effectively prevent violence against early childhood while supporting optimal emotional and social development